2020
DOI: 10.3390/pathogens9040244
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Spread of Classical Swine Fever Virus among South Korean Wild Boars in Areas near the Border with North Korea

Abstract: There has been a rapid increase in the number of classical swine fever (CSF) sero-positive wild boars captured near the demilitarized zone (DMZ), located the border with North Korea. In 2015–2016, few CSFV-positive antibody boars were detected; however, the number has increased steeply since 2017. Most occurred in the northern region of Gyeonggi before spreading slowly to Gangwon (west to east) in 2018–2019. Multi-distance spatial cluster analysis provided an indirect estimate of the time taken for CSFV to spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Cross-reactivity is likely to occur, although not reported in a study investigating seroconversion in a limited number of animals [ 11 ]. The use of CSF marker vaccines in domestic pigs and bait vaccination of wild boar in South Korea just started very recently [ 12 ]. It will be of great interest to learn how robust this DIVA concept works under field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-reactivity is likely to occur, although not reported in a study investigating seroconversion in a limited number of animals [ 11 ]. The use of CSF marker vaccines in domestic pigs and bait vaccination of wild boar in South Korea just started very recently [ 12 ]. It will be of great interest to learn how robust this DIVA concept works under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this CSFV chimera, the complete E rns and signal peptide encoding sequence was replaced by corresponding BVDV sequences [ 11 ]. The vaccine was licensed in South Korea in 2017 and can be applied in domestic pigs as well as in wild boar [ 12 ]. In China, an inactivated vaccine based on a recombinant baculovirus expressing the CSFV E2 protein has been licensed in 2017 and is used by some pig farms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subgenotype 2.1d was firstly isolated from the outbreaks in China in 2014 to 2015 (8) and is reported to cause a chronic or moderate form of infection (9)(10)(11). It has also been detected in South Korea (12,13). A phylogenetic study showed that the CSF virus isolated from the 2018 Japan outbreak index case was different from the strains that had caused previous CSF-outbreaks in Japan (6).…”
Section: Introductionmentioning
confidence: 99%
“…The spread of CSF followed the migration paths of wild boars. The same concern also goes to wild boar populations residing in the demilitarized zone of Korea [ 7 ]. The spatial distance between each CSF notification was about 23 km, the widest radius of outbreak cluster was 20 km [ 2 ], and each outbreak cluster lasted 98–124 days [ 2 ].…”
mentioning
confidence: 99%
“…These data provide a scientific basis on how far and how long the control measure should be imposed. Monitoring the antigen and antibody in wild boars will provide warning for neighboring domestic pigs in those particular settings [ 3 , 7 ].…”
mentioning
confidence: 99%